VALUE CHAIN MANAGEMENT MODEL OF BETONG CHICKEN BREED FOR POVERTY REDUCTION IN THE SOUTHERN BORDER OF THAILAND - Nirunkiat Livkunupakan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This research aims to address poverty in the southern border areas, the goal is Betong chicken is used as a career tool for poor households. The research used the action research was during the period of September 2019 to March 2020 with the total of 275 households, in the southern border, the research was planned to operate in 2 different phases. The first phase is to assess the potential of the farmers, by letting the households in poverty go through a trial of raising 5 Betong chickens. Upon passing the evaluation, 100 households will be selected to go through to the second phase and raise 15 Betong Chickens. At 4-4.5 months old, a saleable male Betong Chicken will weigh around 2-2.5kg and a saleable female Betong Chicken will weigh around 1.3-1.9kg. As for the marketing aspect, individuals have been procured to connect the market opportunity and households in poverty to market Betong Chickens at the price of 100-110 Baht per kilogram, the results show that the cornerstone of any successful poverty alleviation project is building social capital, through jobs creation, education and support. These 3 factors were mistakes made in previous projects which resulted in unsatisfactory results. Based on in-depth analysis of the value chain management model, improvements were made to the primary and supporting activities. Namely, leveraging on university resources and technology, co-operation from various government agencies and providing intuitive knowledge and know-hows.